Effect of Chinese qualification intervention to reduce pain indicators and improving efficiency of ankle injuries for female students - Ibrahim, Hani Khalil (Tanjungpura Journal of Coaching Research, 2025)
Background. Ankle injuries are common among physically active female students and often result in pain, reduced mobility, and limitations in daily activities. Effective rehabilitation approaches are essential to accelerate recovery and restore function. This study aimed to evaluate the effectiveness of an integrated rehabilitation program combining therapeutic exercises with acupuncture in improving ankle joint function. Methods. The study employed an experimental method with two groups: the first received a rehabilitation program using elastic ropes and medicine balls combined with acupuncture, while the second received the same program without acupuncture. Key outcome measures included pain level, ankle joint range of motion, and ability to perform daily activities. Results. Results demonstrated significant improvements in both groups (p < 0.05). However, the group receiving acupuncture achieved greater gains, with a 54% reduction in pain compared to 42% in the control group, a 60% improvement in ankle range of motion compared to 45%, and a 61% improvement in daily activities compared to 49%. Statistical analysis confirmed that the combined program was significantly more effective. Conclusions. In conclusion, integrating acupuncture with therapeutic exercises enhanced rehabilitation outcomes, accelerating recovery and improving quality of life for students with ankle injuries. This study contributes evidence supporting the use of complementary methods in sports rehabilitation. The findings recommend that physical therapy and sports rehabilitation centers adopt combined approaches that integrate traditional Chinese techniques with modern therapeutic exercises.